Reliability, Validity, and Sensitivity to Change of the Lower Extremity Functional Scale in Individuals Affected by Stroke. Issue 12 (19th July 2013) - Verheijde, Joseph L.; White, Fred; Tompkins, James; Dahl, Peder; Hentz, Joseph G.; Lebec, Michael T.; Cornwall, Mark
Abstract : Objective: To investigate reliability, validity, and sensitivity to change of the Lower Extremity Functional Scale (LEFS) in individuals affected by stroke. The secondary objective was to test the validity and sensitivity of a single‐item linear analog scale (LAS) of function. Design: Prospective cohort reliability and validation study. Setting: A single rehabilitation department in an academic medical center. Patients: Forty‐three individuals receiving neurorehabilitation for lower extremity dysfunction after stroke were studied. Their ages ranged from 32 to 95 years, with a mean of 70 years; 77% were men. Methods: Test‐retest reliability was assessed by calculating the classical intraclass correlation coefficient, and the Bland‐Altman limits of agreement. Validity was assessed by calculating the Pearson correlation coefficient between the instruments. Sensitivity to change was assessed by comparing baseline scores with end of treatment scores. Measurements were taken at baseline, after 1‐3 days, and at 4 and 8 weeks. Main Outcome Measurements: The LEFS, Short‐Form‐36 Physical Function Scale, Berg Balance Scale, Six‐Minute Walk Test, Five‐Meter Walk Test, Timed Up‐and‐Go test, and the LAS of function were used. Results: The test‐retest reliability of the LEFS was found to be excellent (ICC = 0.96). Correlated with the 6 other measures of function studied, the validity of the LEFS was found to be moderate to high ( r = 0.40‐0.71). Regarding the sensitivity to change, the mean LEFS scores from baseline to study end increased 1.2 SD and for LAS 1.1 SD. Conclusion: LEFS exhibits good reliability, validity, and sensitivity to change in patients with lower extremity impairments secondary to stroke. Therefore, the LEFS can be a clinically efficient outcome measure in the rehabilitation of patients with subacute stroke. The LAS is shown to be a time‐saving and reasonable option to track changes in a patient's functional status.